Detection of Dermatophyte between Toes of Medical Students Wearing and not Wearing Socks in Universitas Padjadjaran using Direct Microscopic Examination - Magarita, Venna; Sadeli, Ramlan; Gunawan, Hendra (Althea Medical Journal, 2015)
Background: Dermatophytes thrive in warm, humid, and moist areas. Wearing the same socks more than A day is one predisposing factor. The aim of this study is to detect the dermatophyte between the fourth and fifth toes of medical students of Universitas Padjadjaran, who wear and do not wear socks.Methods: This was a cross-sectional descriptive study performed in Microbiology Laboratory of Faculty of Medicine Universitas Padjadjaran from September to October 2013. Direct microscopic examination using 10% Potassium Hydroxide (KOH) was performed on 50 medical students, 25 students who wear socks and 25 students who do not wear socks. The samples were taken from scraped skin between the fourth and fifth toes using the cellophane tape method. The sample size is obtained via stratified random sampling.Results: From all participants, two students (4%) showed positive result of dermatophyte hyphae and 1 student (2%) showed positive result of dermatophyte hyphae and arthrospore. Of these three students, two students wear socks and one student does not wear socks. The two students who wear socks changed their socks more than a day.Conclusions: Dermatophyte was detected in only a few medical students of Universitas Padjadjaran, whoÂ wear and do not wear socks. [AMJ.2015;2(4):480â4]Â DOI:Â 10.15850/amj.v2n4.631